A study on organizational commitment affecting job satisfaction at Air Kelantan Sdn Bhd (AKSB) / Mohamad Hanif Fadhil Nasrudin - Nasrudin, Mohamad Hanif Fadhil (2015)
The purpose of this study is to examine the relationship between components of organizational commitment and job satisfaction among employees Air Kelantan Sdn Bhd in Kota Bharu, Kelantan. Therefore this study could make important contribution to extant research in management and organizational behaviour. In the beginning of this study, the purpose, research question, and the need for the study is given. Then, literature is discussed about organizational commitment and job satisfaction that focusing on the relationship between them. The study generated a 90.0 percent response rate from 100 respondents. The result showed that only affective commitment has significant positive relationship with job satisfaction. Meanwhile, both continuance and normative commitment was not found to have significant positive relationship with job satisfaction.